SIGNIFICANCE OF MICROALBUMINURIA IN HEARING LOSS IN TYPE – 2 DIABETES MELLITUS - SUMATHI.K.; MYTHILI.S.V .; MANJULA DEVI.A.J. (International Journal of Pharma and Bio Sciences, 2014)
Presence of microalbuminuria in diabetes mellitus is one of the diagnostic indicator of diabetic cochleopathy. The aim of this study is to study the significance of microalbuminuria in deafness in type-2 diabetes mellitus & to correlate between microalbuminuria and cochleopathy in type-2 diabetes mellitus. The study was conducted in a sample of 100 diabetic patients attending diabetic outpatient department of tertiary care center for routine check up. Microalbumin (MAL) in human urine was estimated by turbidimetric immunoassay & Hearing Loss by Pure Tone Audiogram. Out of 100 diabetic patients, 58 had microalbumin in urine & 46 had hearing loss. Out of 46 diabetic patients with hearing loss, 42 had microalbuminuria. In this study, 46% percentage of diabetic people were found to be associated with hearing loss. Microalbuminuria was found in 58% of the diabetics & 91.3% of diabetic cochleopathy had microalbuminuria. Thus, early detection of microalbuminuia in diabetic patients can help in prevention & progression of hearing loss which is irreversible.